Hybrid antibacterial agents. - Lin, Jiawen. (2012)
The rising antibiotic resistance of bacteria is posing a challenge towards clinical treatment with many currently available antibiotics losing their initial efficacy. There is, therefore, an urgent need to identify new therapeutic agents with the ability to target these resistant bacterial strains. This project proposes an innovative strategy via a combinatorial approach to link two commonly used antibiotics, penicillin and vancomycin, via an antimicrobial peptide (AMP) to generate a hybrid antibacterial agent. The cooperative effects of the three entities could potentially overcome bacterial resistance, in addition, enhancing other properties in terms of efficiency, stability, and toxicity. Several derivatives of the penicillin moiety were successfully synthesized by incorporating various components to enhance structural flexibility and antimicrobial activity in preparation for chemical ligation. However, further progress was impeded by limited yield and purification difficulty from solid- and liquid-phase peptide synthesis method respectively. The synthesis of AMP with sequence resembling that of V2-monomer, an active AMP, was obtained through similar solid-phase method. The progress of this project had reached an important juncture where chemical ligation was imminent, ensuing by assays to determine antibacterial properties.